The Sensitivity Prediction of Neoadjuvant Chemotherapy for Gastric Cancer - Sun, Juan; Wang, Xianze; Zhang, Zimu; Zeng, Ziyang; Ouyang, Siwen; Kang, Weiming (Frontiers in Oncology, 2021)
The overall efficacy of neoadjuvant chemoradiotherapy (NACT) for locally advanced gastric cancer (LAGC) has been recognized. However, the response rate of NACT is limited due to tumor heterogeneity. For patients who are resistant to NACT, not only the operation timing will be postponed, patients will also suffer from the side effects of it. Thus, it is important to develop a comprehensive strategy and screen out patients who may be sensitive to NACT. This article summarizes the related research progress on the sensitivity prediction of NACT for GC in the following aspects: microRNAs, metabolic enzymes, exosomes, other biomarkers; inflammatory indicators and imageological assessments. The results showed that there were many studies on biomarkers, but no unified conclusion has been drawn. The inflammatory indicators are related to the survival and prognosis of patients under NACT. For imageological assessments such as CT, MRI and PET, with careful integration and optimization, they will have unique advantages in early screening for patients who are sensitive to NACT.